Calvin and English Calvinism to 1649 - Kendall, R.T. (U.K. Paternoster, 1997)
Includes bibliographical references and indexes.
Originally written as the author's thesis, Oxford University. First published in the U.K. 1981 by Oxford U.P.
Keywords: Calvin, John -- 1509-1564; Reformation; Calvinism